Professionals’ views on the use of smartphone technology to support children and adolescents with memory impairment due to acquired brain injury - Plackett, Ruth; Thomas, Sophie; Thomas, Shirley A. (Taylor and Francis Group, 2017)
Purpose: To identify from a health-care professionals’ perspective whether smartphones are used by children and adolescents with acquired brain injury as memory aids; what factors predict smartphone use and what barriers prevent the use of smartphones as memory aids by children and adolescents. Method: A cross-sectional online survey was undertaken with 88 health-care professionals working with children and adolescents with brain injury. Results: Children and adolescents with brain injury were reported to use smartphones as memory aids by 75% of professionals. However, only 42% of professionals helped their clients to use smartphones. The only factor that significantly predicted reported smartphone use was the professionals’ positive attitudes toward assistive technology. Several barriers to using smartphones as memory aids were identified, including the poor accessibility of devices and cost of devices. Conclusion: Many children and adolescents with brain injury are already using smartphones as memory aids but this is often not facilitated by professionals. Improving the attitudes of professionals toward using smartphones as assistive technology could help to increase smartphone use in rehabilitation.